Interrogating Poetic Thinking in Antonio Méndez Rubio's "Question" Poems. - Cahill, Paul (Hispanic Review)
This article focuses on an important subset of the work of Spanish poet, critic, and theorist Antonio Méndez Rubio (1967–) and explores the often overlooked role that questions play in lyric poetry. Following earlier work by Spanish and Latin American poets like Pablo Neruda, Francisco Pino, José Hierro, and Juan Gelman, Méndez Rubio's poems consisting entirely of questions span nearly two decades (1998–2017) and illustrate the potential that questions have as spaces from which to develop, explore, and interrogate poetic thinking. Establishing a dialogue between question poems that focus on writing, speaking, and expression and theoretical work on lyric structures (Culler), poetic attention (Alford), poetic thinking (Vendler), lyric address (Waters), and the use of questions in poetry (Jauss and Wolfson) helps us rethink the way we approach poetry in general and engage with the concepts it constructs, presents, and examines.